Isolation Of Anverene From The Antarctic Peninsula Red Algae (Plocamium Cartilaginium) - Pasaribu, Albert (2010)
An Anverene (1) was isolated from the chloroform extract of the Antarctic red algae Plocamium cartilagium. Structural studies of this compound were conducted using contemporary NMR and mass spectral techniques. In this paper, the contribution of compound 1 to pharmacological effect will be discussed.